Late Antiquity: Decadence or “Democratization” of Culture? - Milinović, Dino (Poznańskie Studia Slawistyczne, 2019)
In our age “without the emperor”, fascination with empires and with the emperor mystique continues. Take for witness Tolkien and his Return of the King, the third sequel of The Lord of the Rings, or the television serial Game of Thrones. In the background, of course, is the lingering memory of the decline and fall of the Roman Empire, “a revolution which is still felt by all nations of the world”, to quote Edward Gibbon. It comes as a surprise that in this dramatic moment of its history, in times marked by political, economic and spiritual crisis that shook the very foundations of the Empire during the 3rd century, historians and art historians have recognized the revival of plebeian culture (arte plebea, kleinbürgerliche Kultur). It was the Italian historian Santo Mazzarino, talking at the XI International Congress of the Historical Sciences in Stockholm in 1960, who introduced a new paradigm: the “democratization of culture”. In the light of the historical process in the late Roman Empire, when growing autocracy, bureaucracy, militarization and social tensions leave no doubt as to the real political character of the government, the new paradigm opened up fresh approaches to the phenomenon of decadence and decline of the Roman world. As such, it stands against traditional scenario of the “triumph of barbarism and Christianity”, which was made responsible for the fall of the Roman Empire and the eclipse of the classical civilization of ancient Greece and Rome. It is not by accident that the new paradigm appeared around the middle of the 20th century, at the time when European society itself underwent a kind of “democratization of culture”, faced with the phenomenon of mass culture and the need to find new ways of evaluating popular art. Today, more than anything else, the notion of “democratization of culture” in late Roman Empire forces us to acknowledge a disturbing correspondence between autocratic and populist forms of government. It may come as a shock to learn that the very emperors who went down in Roman history as villains and culprits (such as Caligula, Nero or Commodus), were sometimes considered the most “democratic” among Roman rulers. Do we need to feel certain unease at this historical parallel?